The fatigue behaviour of three-dimensional stress concentrations - Bellett, Daniel (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2003)
The fatigue behaviour of complex three-dimensional notched components is a subject of great practical interest to industrial engineers. Unfortunately, the analysis of this type of feature presents problems for most assessment methods, which have been developed on the basis of standard two-dimensional fatigue specimens. This work is essentially an investigation of several factors that are considered important and unique to the assessment of this type of feature. It has been demonstrated experimentally that the fatigue assessment methods advocated by Taylor [1996; 1999], and indeed most assessment methods, result in conservative predictions for certain three-dimensional stress concentration features. These are typically very localised stress concentrations characterised by high stress gradients in all directions and also stress concentrations characterised by low constraint. Three possible explanations have been proposed and investigated. These have been termed the shape ejfect, the constraint effect and the stressed volume effect. The shape effect is based on the observation that if failure is forced to occur at a point or small region, via geometrical constraints, it will have a semi-elliptical crack front. It is proposed that even at the so-called fatigue limit, crack shape can affect the life of a component through the growth of non-propagating cracks. It is shown that a simple correction factor, based on the crack shape, can be applied to account for this.
Keywords: Mechanical Manufacturing Engineering, Ph.D.; Ph.D. Trinity College Dublin